2018
DOI: 10.1002/ange.201802266
|View full text |Cite
|
Sign up to set email alerts
|

Novel Oil‐in‐Water Emulsions Stabilised by Ionic Surfactant and Similarly Charged Nanoparticles at Very Low Concentrations

Abstract: Novel oil-in-water (O/W) emulsions are prepared which are stabilised by ac ationic surfactant in combination with similarly charged alumina nanoparticles at concentrations as low as 10 À5 m and 10 À4 wt %, respectively.T he surfactant molecules adsorb at the oil-water interface to reduce the interfacial tension and endowd roplets with charge ensuring electrical repulsion between them, whereas the charged particles are dispersed in the aqueous films between droplets retaining thickl amellae,r educing water drai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 39 publications
(78 citation statements)
references
References 40 publications
4
74
0
Order By: Relevance
“…We note that some Pickering emulsions can also be stabilized when the interfacial coverage by particles is quite low. [36,37] Here, we believe that only NaDC molecules adsorb at the oil-water interface with silica particles dispersed in the continuous phase between droplets [31][32][33][34][35] producing an oil-indispersion emulsion [35] as shown by the SEM and fluorescence microscopy images (Figures 2 and S7). It was further observed that this strategy of improving the emulsifying ability of BS by addition of silica particles is universal for other BS.…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…We note that some Pickering emulsions can also be stabilized when the interfacial coverage by particles is quite low. [36,37] Here, we believe that only NaDC molecules adsorb at the oil-water interface with silica particles dispersed in the continuous phase between droplets [31][32][33][34][35] producing an oil-indispersion emulsion [35] as shown by the SEM and fluorescence microscopy images (Figures 2 and S7). It was further observed that this strategy of improving the emulsifying ability of BS by addition of silica particles is universal for other BS.…”
Section: Resultsmentioning
confidence: 81%
“…The fluorescence image (particles labelled green in Figure S7) also proves the position of the particles is mainly in the aqueous continuous phase. [31][32][33][34][35] This microstructure is different from that of Pickering emulsions stabilized by NaDC and positively charged alumina nanoparticles (Figure 2d), in which particles attach to the oilwater borders forming winkled films on the surfaces of dried oil droplets. We note that some Pickering emulsions can also be stabilized when the interfacial coverage by particles is quite low.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…4. The initial velocities were set for copper atoms that were consistent with the temperature of (300 K) 5. Then another 500000 steps of equilibration were performed in the NPT.…”
Section: Simulation Detailsmentioning
confidence: 99%
“…It is well known that the former is stabilized in the colloids due to steric forces because of the presence of the capping agent. On the other hand, the uncapped NPs are electrostatically stabilized due to the native surfaces [4][5][6] . Although the capping agents help in the steric stabilization of the NPs in liquids, they reduce the direct interaction of NPs with each other as well as the space for preferential adsorptions of ions/molecules on the surfaces of the NPs.…”
Section: Introductionmentioning
confidence: 99%